Can Trait Mindfulness Improve Job Satisfaction? The Relationship Between Trait Mindfulness and Job Satisfaction of Preschool Teachers: The Sequential Mediating Effect of Basic Psychological Needs and Positive Emotions - Song, Zhanmei; Pan, Baocheng; Wang, Youli (Frontiers in Psychology, 2021)
Objective: This study aims to explore the relationship between basic psychological needs and positive emotions of preschool teachers between trait mindfulness and job satisfaction. Methods: Three hundred and ninety-eight preschool teachers were tested with mindfulness attention awareness scale, basic psychological needs scale, positive emotion scale, and job satisfaction scale. Results: Preschool teachers trait mindfulness can predict job satisfaction (β = 0.265, p < 0. 001). Preschool teachers trait mindfulness has an indirect impact on job satisfaction through basic psychological needs (β = 0.059, p = 0.002), and preschool teachers trait mindfulness has an indirect impact on job satisfaction through positive emotions (β = 0.123, p < 0. 001). In addition, basic psychological needs and positive emotions play a sequential intermediary role between preschool teachers trait mindfulness and job satisfaction (β = 0.017, p < 0. 001). Conclusion: Basic psychological needs and positive emotions play a sequential mediating role between preschool teachers trait mindfulness and job satisfaction, and this sequential mediating effect accounts for a high proportion of the total effect.